“Prevelance Of Preterm Premature Rupture Of Membrane And Its Associated Factors Among The Pregnant Women In The Selected Tertiary Carehospital, Bhubaneswar, Odisha” (Journal of Pharmaceutical Negative Results, 2023)
BACKGROUNDPreterm premature rupture of the membranes (PPROM) is the spontaneous rupture of the fetal membranes and amniotic fluid loss prior to the onset of labour in a pregnancy earlier to 37 weeks of gestation, described as painless flow of fluid which escape from vagina in the absence of consistent painful uterine contraction. Spontaneous rupture of membranes is a normal component of labor and delivery.Method:-A descriptive clinical study was done among 446 pregnant mothers in between 28-37 weeks of gestation from the Department of Obstetrics and Gynecology ward, OPD and Labor room at Pradyumna Bal Memorial Hospital KIMS, Bhubaneswar, Odisha. Consecutive sampling technique was used to select the samples. A self-structured questionnaire on Preterm Premature Membrane Rupture was employed, and data were obtained via the Interview technique.Results: After screening among 446 mothers, 6 mothers were having PPROM and there was a 100% response rate. The combined prevalence of premature membrane rupture among pregnant women at PBMH, KIMS, Bhubaneswar, Odisha was 1.34%.Factors related with premature membrane rupture were identified like Obstetrical variables and risk factors as evidenced by- Accidental fall (P = 0.01), Lifting of heavy objects (P= 0.01), Urinary tract infection (P=0.01),Anemia (P= 0.02), Type of vaginal discharge (P=0.04) and Abnormal vaginal discharge (P =0.02) ,gestational weeks (P=0.02), amniotic fluid index as per USG (P= 0.02),color of amniotic fluid (P= 0.01), sign of true labor pain (P=0.01), presentation (P= 0.01) and gestational diabetes mellitus (P= 0.01).Conclusion:-PPROM is a significant obstetric problem. The prevalence rate of preterm premature rupture of membrane was 1.34% which is less in comparison to the National prevalence i.e. 3-4% as per WHO. PPROM is one of the leading causes of premature birth and can increase both maternal and perinatal morbidity and mortality. As a result, extensive prenatal monitoring is required during antenatal care as well as early screening, diagnosis, and therapy to decrease the PPROM.